2008
DOI: 10.1016/j.cmet.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Stat3 Signaling in AgRP Neurons Promotes Locomotor Activity

Abstract: Leptin, an adipocyte-derived hormone, acts on hypothalamic neurons located in the arcuate nucleus (ARC) of the hypothalamus to regulate energy homeostasis. One of the leptin-regulated neuronal subtypes in the ARC are agouti-related peptide (AgRP)-expressing neurons, which are involved in the regulation of food intake and are directly inhibited by leptin. Leptin activates the signal transducer and activator of transcription 3 (Stat3), but the role of Stat3 in the regulation of AgRP neurons is unclear. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 216 publications
(257 reference statements)
4
84
1
2
Order By: Relevance
“…The contribution of the melanocortin system to leptin effects on energy expenditure and body weight is supported by numerous pharmacological studies (98)(99)(100). A number of parallel genetic studies similarly demonstrated that locomotor activity, temperature, or energy expenditure are changed in mice with modified expression of OB-Rb or its signaling molecular partners in ARH neurons (17,20,55,79,101,102).…”
Section: Body Weight Body Weight Control Is Exceptionally Complicatedmentioning
confidence: 78%
“…The contribution of the melanocortin system to leptin effects on energy expenditure and body weight is supported by numerous pharmacological studies (98)(99)(100). A number of parallel genetic studies similarly demonstrated that locomotor activity, temperature, or energy expenditure are changed in mice with modified expression of OB-Rb or its signaling molecular partners in ARH neurons (17,20,55,79,101,102).…”
Section: Body Weight Body Weight Control Is Exceptionally Complicatedmentioning
confidence: 78%
“…Body fat content was measured in vivo by NMR using a minispec mq7.5 (Bruker Optik) as previously described (38).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that Stat3-C POMC mice showed a tendency toward reduced energy expenditure compared with controls, although this effect did not reach statistical significance (Mesaros et al, 2008). To further analyze the mechanism underlying the mild obesity observed in Stat3-C POMC mice, we directly measured food intake in these mice.…”
Section: Stat3-c Pomc Mice Exhibit Increased Food Intake and Decreasementioning
confidence: 99%